Second Generation of Biodiesel Production from Indonesian Jatropha Oil by Continuous Reactive Distillation Process - Arief Budiman; Ratna D Kusumaningtyas; Sutijan Sutijan; Rochmadi Rochmadi; Suryo Purwono (ASEAN Journal of Chemical Engineering, 2010)
The batch process of biodiesel production deals with problems related to the labor and separation cost since it is slow, entailing several separation steps, labor intensive, and not suitable for a very large-scale production. Therefore, a second generation process technology for biodiesel should be developed. In this work, a continuous transesterification using reactive distillation was proposed. The goal was to bring in a more efficient reactor system by combining chemical reactions and separation simultaneously in one unit. In this work, a laboratory-scale Reactive Distillation was applied for the biodiesel synthesis from the Indonesian refined jatropha oil in the presence of NaOH catalyst. The experimental investigation demonstrated the effects of the temperature, catalyst loading, and molar ratio of the reactants. The best result was achieved on the process conducted at the reaction temperature of 65 ºC with molar ratio of methanol to triglycerides of 10:1 and catalyst loading of 0.75% w/ w oil. The reaction conversion was 94.83% and methyl ester content of the product was 99.27%. The fuel characteristic of biodiesel agreed with the Indonesian national standard and ASTM specification.